2014
DOI: 10.1002/wnan.1283
|View full text |Cite
|
Sign up to set email alerts
|

SERS Nanosensors and Nanoreporters: Golden Opportunities in Biomedical Applications

Abstract: This article provides an overview of recent developments and applications of surface-enhanced Raman scattering (SERS) nanosensors and nanoreporters in our laboratory for use in biochemical monitoring, medical diagnostics, and therapy. The design and fabrication of different types of plasmonics-active nanostructures are discussed. The SERS nanosensors can be used in various applications including pH sensing, protein detection, and gene diagnostics. For DNA detection the 'Molecular Sentinel' nanoprobe can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 113 publications
0
75
0
Order By: Relevance
“…SERS is one technique that can enhance the Raman signal by several orders of magnitude by amplifying the electron cloud density around metallic nanostructures [99][100][101]. SERS signal enhancement is achieved through two distinct mechanisms: electromagnetic enhancement and chemical enhancement [100,[102][103][104]. For both mechanisms to occur simultaneously, an analyte must be adsorbed onto or reside very close to a dielectric (often metallic) surface [90].…”
Section: Surface Enhanced Raman Spectroscopy (Sers) and Its Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…SERS is one technique that can enhance the Raman signal by several orders of magnitude by amplifying the electron cloud density around metallic nanostructures [99][100][101]. SERS signal enhancement is achieved through two distinct mechanisms: electromagnetic enhancement and chemical enhancement [100,[102][103][104]. For both mechanisms to occur simultaneously, an analyte must be adsorbed onto or reside very close to a dielectric (often metallic) surface [90].…”
Section: Surface Enhanced Raman Spectroscopy (Sers) and Its Potentialmentioning
confidence: 99%
“…For chemical enhancement to occur, a molecule must be able to be bound directly to the surface of the metal so that there is a charge-transfer structure generated, i.e. an electron-hole pair that can mediate the transfer of energy from the metal directly to the molecular bonds of the analyte [103,104].…”
Section: Surface Enhanced Raman Spectroscopy (Sers) and Its Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmonics-stimulated and optically modulated delivery of nanoparticles into brain tumor in live animals was demonstrated and gold nanoparticle based photothermal treatment of tumor vasculature may stimulate inflammasomes activity, thus increasing the permeability of the blood brain barrier. The imaging method using TPL of gold nanoparticles provides an unprecedented spatial selectivity for targeted nanoparticles delivery to tumor tissue [20].…”
Section: Sers and Tersmentioning
confidence: 99%
“…A special type of metallic nanoparticles, called 'plasmonic' nanoparticles, has received great interest because they exhibit enhanced optical and electromagnetic properties. Our fundamental studies of various plasmonic structures [8][9][10] and applied development of plasmonic nanoplatforms have led to a wide variety of applications ranging from chemical sensing [10][11][12] to cancer diagnostics [13][14][15][16][17] and therapy using nanoparticle-mediated photothermal treatment [15,[18][19][20]. Recently, we demonstrated that the use of plasmonic gold nanostars (GNS) in combination with immunotherapy -a treatment we referred to as Synergistic Immuno Photothermal Nanotherapy (SYMPHONY) -can dramatically enhance the efficacy of immunotherapy.…”
mentioning
confidence: 99%